CERITA RAKYAT KYAI KARSOREDJO DUKUH PANDANAN: TINJAUAN SOSIOLOGI SASTRA DAN NILAI RELIGI SERTA RELEVANSINYA SEBAGAI MATERI AJAR DI SMP - Silotika, Imas; Rahmat, Rahmat; Suyitno, Suyitno (Universitas Sebelas Maret, 2017)
This research aims to describe and explain the elements of sociology of literature, religious values, and the relevance of folklore Kyai Karsoredjo hamlet Pandanan as an alternative Javanese teaching materials for VII grade student in junior High Scool. The research used descriptive qualitative research method with folklore approach, sociology of literature and religious values. The conclucion of this research is the result of sociology of literature of Kyai Karsoredjo folklore in Pandanan region that indicates the social values contained in the story such as: mutual cooperation, cooperation, helping each other are dominant. Meanwhile, religious values are contained in the folklore such as: fasting, alms and pilgrimage. In addition, it is relevant as a teaching material of Javanese class of VII student in junior high school.